VD_FINDINFO Décision / 2015 / 438 vom 4. Juni 2015 - VD Tribunal cantonal (2015)
SÉQUESTREMESURE PROVISIONNELLE, MOYEN DE PREUVE, CADAVRE, RESTITUTIONEN GÉNÉRAL | 253 al. 3 CPP (CH), 267 al. 1 CPP (CH)